PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE AND MATCH BERBANTUAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPA KELAS VIII - A SMPN 6 SUMENEP - Yani Fadariyah (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2020)
This study aims to increase student motivation, by using the cooperative learning model type a make a match assisted by audio visual media in science subjects class VIII-A SMPN 6 SUMENEP. This type of research is a classroom action research (CAR) with the approach used is a qualitative and quantitative approach that is descriptive and without using statistical analysis. The research subjects studied were SMP Negeri 6 Sumenep students in class VIII-A in the odd semester of 2017/2018 with 23 students consisting of 12 female students and 11 male students. Data collection instruments were carried out using sheets of the implementation of learning activities and observation sheets of student motivation. The results of student learning motivation in science subjects using the make a match type of cooperative learning model assisted by audio-visual media using card media distributed during learning and group formation to find partners makes students active and enthusiastic so that their motivation to learn increases. This can be seen from the percentage in cycle 1 students' learning motivation is still in the moderate category (57%). In cycle II it has increased, so it rises to the good category (76.5%).